A NOTE ON HERMITE-HADAMARD INEQUALITIES FOR PRODUCTS OF CONVEX FUNCTIONS VIA RIEMANN-LIOUVILLE FRACTIONAL INTEGRALS - Chen, Feixiang (Italian Journal of Pure and Applied Mathematics, 2014)
In this paper, we obtain some new Hermite-Hadamard type inequalities for products of convex functions via Riemann-Liouville integrals. We conclude that Our methods considered here may be a stimulant for further investigations concerning Hermite-Hadamard type inequalities for products of various kinds of convex functions involving Riemann-Liouville fractional integrals.